11
In this case, 22 would have the value of 11.
an = an-1 + d term ar-1 = 11 difference d = -11 ar = ar-1 + d = 11 - 11 = 0 The term 0 follows the term 11.
The nth term of the sequence is 2n + 1.
The given sequence is an arithmetic sequence with a common difference of 7 (18-11=7, 25-18=7, and so on). To find the nth term of an arithmetic sequence, you can use the formula: a_n = a_1 + (n-1)d, where a_n is the nth term, a_1 is the first term, n is the position of the term, and d is the common difference. In this case, the first term a_1 is 11 and the common difference d is 7. So, the nth term of this sequence is 11 + (n-1)7, which simplifies to 11 + 7n - 7, or 7n + 4.
11
The given sequence is 11, 31, 51, 72 The nth term of this sequence can be expressed as an = 11 + (n - 1) × 20 Therefore, the nth term is 11 + (n - 1) × 20, where n is the position of the term in the sequence.
In this case, 22 would have the value of 11.
an = an-1 + d term ar-1 = 11 difference d = -11 ar = ar-1 + d = 11 - 11 = 0 The term 0 follows the term 11.
The nth term of the sequence is 2n + 1.
I believe the answer is: 11 + 6(n-1) Since the sequence increases by 6 each term we can find the value of the nth term by multiplying n-1 times 6. Then we add 11 since it is the starting point of the sequence. The formula for an arithmetic sequence: a_{n}=a_{1}+(n-1)d
The given sequence is an arithmetic sequence with a common difference of 7 (18-11=7, 25-18=7, and so on). To find the nth term of an arithmetic sequence, you can use the formula: a_n = a_1 + (n-1)d, where a_n is the nth term, a_1 is the first term, n is the position of the term, and d is the common difference. In this case, the first term a_1 is 11 and the common difference d is 7. So, the nth term of this sequence is 11 + (n-1)7, which simplifies to 11 + 7n - 7, or 7n + 4.
The nth term in this sequence is 4n + 3.
94-1-6-11
3 11
It seems each term(except the first one obviously) is generated by adding 11 to previous one. 4 15 = 4 + 11 26 = 15 + 11 37 = 26 + 11 The next term in the sequence will be then: 48 = 37 + 11
One of the infinitely many possible rules for the nth term of the sequence is t(n) = 4n - 1